PERAN EXPERIENTIAL VALUE DALAM MEMEDIASI PENGARUH EXPERIENTIAL MARKETING TERHADAP REPURCHASE INTENTION - Wayan Febri Astari; Komang Agus Satria Pramudana (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2016)
The objective of this research is to analyze experiential value role in mediating the effect of experientialmarketing on repurchase intention, through comprehensive review of previous studies and survey at the GustoGelato and Cafe. This study uses a quantitative approach in form of associative. The sample used were 185respondents which was collected by purposive sampling method. Data were collected through questionnaireand interview. The analysis technique used to test the hypothesis is Structural Equation Modeling (SEM) withAMOS 16.00 software. The results of this study indicates that the experiential marketing has a positive andsignificant effects on experiential value and repurchase intention. In addition, the study also found thatexperiential marketing has a significant influence towards repurchase intention with experiential value asmediating variable.